(untitled) - Bercot, David W.; (1950-...) (U.S.A, 1998)
A compendium of quotations culled from the ten volume Ante-Nicene Fathers and arranged by subject for quick reference. The quotes include comments on 700 theological, moral, and historical topics from prominent figures such as Origen, Clement of Alexandria, Clement of Rome, and Hippolytus.
Keywords: Christianity -- ca. 0030-0600 (Early Church) -- dictionaries